Routledge handbook on Islam in Asia - Formichi, Chiara (Routledge, Taylor & Francis Group, 2022)
"The Routledge Handbook of Islam in Asia offers both new and established scholarship on Muslim societies and religious practices across Asia, from a variety of interdisciplinary angles, with chapters covering South, Central, East and Southeast Asia, as well as Africa-Asia connections. Presenting work grounded in archival, literary, and ethnographic inquiry, contributors to this handbook lend their expertise to paint a picture of Islam as deeply connected to and influenced by Asia, often by-passing or reversing relationships of power and authority that have placed 'Arab' Islam in a hierarchically superior position vis-à-vis Asia. This handbook is structured in four parts, each representing an emergent area of inquiry: Frames Authority and Authorizing Practices Muslim Spatialities Imaginations of Piety Dislodging ingrained assumptions that Asia is at the periphery of Islam - and that Islam is at the periphery of Asia's cultural matrix - this handbook sets an agenda against the 'centre-periphery' dichotomy, as well as the syncretism paradigm that has dominated conversations on Islam in Asia. It thus demonstrates possibilities for new scholarly approaches to the study of Islam within the 'Asian context'. This ground-breaking handbook is a valuable resource to students and scholars of Asian studies, religious studies, and cultural studies more broadly"--
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Islam; Südostasien; Südasien; Asien